Synthesis, characterization, and antibacterial properties of selected glucose derivatives - Sadiq, Hawraa M. (Current Issues in Pharmacy and Medical Sciences, 2026)
A multistep synthetic route was developed for the preparation of a diazido compound starting from methyl α-D-glucopyranoside 1. The synthesis began with protection of the C-4 and C-6 hydroxyl groups using a benzylidene protecting group. Compound 2 was subsequently reacted under phase-transfer conditions with bis (2-chloroethyl) ether to afford the bis-chloro derivative 3. Compound 3 was then converted into a more effective leaving-group derivative, namely the iodide compound 4 . Finally, nucleophilic substitution of the iodide groups with azide ions was carried out by reacting compound 4 with sodium azide in dimethylformamide, yielding the target diazido derivative 5.In addition, the synthesized compounds were evaluated for antibacterial activity against Escherichia coli and Staphylococcus aureus using the agar well diffusion method. The results demonstrated moderate antibacterial activity against both tested strains. Structural characterization of all synthesized compounds was performed using infrared (IR) spectroscopy and nuclear magnetic resonance spectroscopy (1H NMR and 13C NMR).